2011
DOI: 10.1074/jbc.m110.179382
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Bone Morphogenetic Protein 4 Signaling Leads to Glomerulosclerosis That Mimics Diabetic Nephropathy

Abstract: Diabetic nephropathy (DN) is the most common cause of chronic kidney disease. We have previously reported that Smad1 transcriptionally regulates the expression of extracellular matrix (ECM) proteins in DN. However, little is known about the regulatory mechanisms that induce and activate Smad1. Here, bone morphogenetic protein 4 (Bmp4) was found to up-regulate the expression of Smad1 in mesangial cells and subsequently to phosphorylate Smad1 downstream of the advanced glycation end product-receptor for advanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 49 publications
(47 reference statements)
2
45
0
Order By: Relevance
“…Generally, BMP2/4 may be considered as inflammatory markers in several metabolic tissues. Under diabetic conditions, expression of BMP2 or BMP4 has been reported to increase in the arteries, kidney, bones and islets [4,14,18,19]. Increased BMP4 expression was reflected by increased circulating levels of BMP4 in type 2 diabetic patients in one study [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, BMP2/4 may be considered as inflammatory markers in several metabolic tissues. Under diabetic conditions, expression of BMP2 or BMP4 has been reported to increase in the arteries, kidney, bones and islets [4,14,18,19]. Increased BMP4 expression was reflected by increased circulating levels of BMP4 in type 2 diabetic patients in one study [13].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, deficiency of inhibitor of differentiation 1 (Id1), encoding a central BMP-regulated transcription factor, resulted in enhanced insulin secretion and protection from diet-induced glucose intolerance, suggesting that BMPs and ID1 normally inhibit adult beta cell function [17]. BMPs are both released from and affect several metabolically relevant tissues, including fat, liver and kidney, thus adding to the complexity of the role of BMPs in metabolism [14,18,19]. To characterise the direct effects of BMPs on beta cells, we recently reported BMP4-mediated inhibition of beta cell proliferation and repression of GSIS from mouse, rat and human islets [4].…”
Section: Introductionmentioning
confidence: 99%
“…BMPs have a critical role in kidney development as evidenced by data showing that BMP-7 null mice are postnatal lethal due to various developmental abnormalities including kidney agenesis [6,7]. Whereas BMP-4 has been shown to contribute to renal fibrosis, conflicting evidence exists for the pro-or anti-fibrotic role of BMP-2 in this process [8][9][10][11]. BMP-7 is thought of as anti-fibrotic, and has been the focus of many groups who demonstrated its anti-fibrotic activity in models of diabetic nephropathy and other kidney fibrotic diseases [5,[12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Although a previous report indicated that this promoter could be transactivated in glomerular epithelial cells (16), another report showed that the transgene under this promoter is expressed ubiquitously in glomeruli (17); therefore, it could still work in mesangial cells. Transgenic mice expressing SMAD1 were generated as described (18). Integration of the transgene into host genome was confirmed by Southern blot analysis of DNA using a 32 P-labeled SMAD1 cDNA fragment as a probe (Fig.…”
Section: Generation Of Smad-overexpressing Micementioning
confidence: 99%